DETERMINATION OF THE BIOACTIVE COMPONENTS OF Abutilon indicum Linn. - KUMAR AMIT; SAXENA GYANENDER (International Journal of Pharma and Bio Sciences, 2013)
Abutilon indicum Linn. is used in the treatment of various ailments either direct or in combination with other plants in many forms such as powder or liquid. This plant is the major source of various ayurvedic medicines, being made in ayurvedic pharmacies throughout the country. Looking the wider use of plant from the literature survey, it has been found that not much work has been carried out on this plant, so a detailed study has been undertaken for chemical investigation. For this purpose extraction, isolation and identification of medicinally valued materials has been carried out. 400 g shade dried powdered roots of Abutilon indicum Linn. were extracted with ethyl alcohol (95%) in a soxhlet extractor. The extract was filtered and the solvent distilled off leaving behind the extracted material. By the TLC, column separation two compounds have been separated and identified by melting points and interpretation of the peaks, matching the graphs with standards of the same compound. One compound is gallic acid in this four peaks obtained, one at 6.93 another at 8.83, 9.20 and 12.24. Another compound was β-sitosterol, from 0-7ï¤ obtained at 0.70, 0.81, 0.84, 0.85, 0.92, 1.01, 3.52 and 5.36 by all these peaks the compound was β-sitosterol. The melting point of compound is 246-249oC. The probable compound is gallic acid. The spectra matched with those of standard reference. The IR and NMR spectra supported the formation of the compounds. The melting point of compound is 135-1360C. The spectra’s matched well with standard references.